Avaliação de risco e análise da profilaxia para tromboembolismo venoso em pacientes no período perioperatório - Larissa Maria Spanó Nakagawa (2020)
NAKAGAWA, L. M. S. Risk assessment and prophylaxis analysis for venous thromboembolism in perioperative period. 67 f. Dissertation (Masters in Nursing) - Nursing School, Federal University of Minas Gerais, Belo Horizonte, 2020. Introduction: Venous Thromboembolism (VTE) is a disease of high prevalence worldwide, and along with pulmonary embolism, represents the most preventable cause of death in hospitalized patients. Surgical patients are even more susceptible to the disease, and in the absence of prophylaxis, 10 to 30% of those patients may be diagnosed with Venous Thromboembolism in the absence of prophylaxis. Objective: Assess the risk and analyze the prophylaxis for venous thromboembolism in patients in the perioperative period. Method: An open cohort study, in three moments of evaluation – before, during and after the surgical procedure. The study site was in the surgical center and the surgical inpatient units of a University Hospital in the state of Minas Gerais. Patients selected have undergone elective surgery have stayed a minimum of 24 hours in the institution. The risk assessment and prophylaxis analysis for venous thromboembolism were performed using the Caprini risk assessment model. Data collection occurred in three phases. First phase was during the preoperative period. Second phase was during the intraoperative period, until the moment the patient is draped. The third phase was during the first 24 hours after surgery in the inpatient units. In the data analysis, correlation of Mann-Whitney, Kruskal-Wallis, Nemenyi and Spearman tests have been used. Results: The final sample consisted of 86 patients, most of them female, aged between 41 and 60, assigned ASA II physical status (according to American Society of Anesthesiologists). The average duration of the anesthetic procedure for those patients was 223,84 minutes. From that sample, 46 (53,49%) patients were identified as being at high risk for venous thromboembolism, 28 (32,55%) at moderate risk and 12 (13,95%) at low risk for the disease. A univariate analysis, the selected variables (p-value ≤ 0,25) were age, race, body mass index, ASA Physical Status Classification System, size of surgery, surgical specialty, identified risk for venous thromboembolism and body weight. In the multivariate analysis final model, there was a significant influence of certain variables which are age, size of surgery, risk for venous thromboembolism and body weight. Conclusion: This research demonstrated the predominance of surgical patients at high risk for venous thromboembolism, the existence of an average of 2.1 risk factors per patient, a low rate of prophylaxis for prevention in the intraoperative and after surgery and a elevated time interval for patients to begin ambulation. It is concluded that a necessity of implementation of protocols that promote prophylactic measures of venous thromboembolism for patients in the perioperative period. Keywords: Venous Thromboembolism. Surgical Procedure. Surgical Patients. Perioperative Period.